Secretion of LamB-LacZ by the Signal Recognition Particle Pathway of Escherichia coli - Bowers, Christina Wilson (American Society for Microbiology, 2003)
LamB-LacZ fusion proteins have classically been used in studies of the general secretion pathway of Escherichia coli. Here we describe how increasing signal sequence hydrophobicity routes LamB-LacZ Hyb42-1 to the signal recognition particle (SRP) pathway. Secretion of this hydrophobic fusion variant (H*LamB-LacZ) was reduced in the absence of fully functional Ffh and Ffs, and the translocator jamming caused by Hyb42-1 was prevented by efficient delivery of the fusion to the periplasm. Finally, we found that in the absence of the ribosome-associated chaperone, trigger factor (Tig), LamB-LacZ localized to the periplasm in a SecA-dependent, SRP-independent fashion. Collectively, our results provide compelling in vivo evidence that there is an SRP-dependent cotranslational targeting mechanism in E. coli and argue against a role for trigger factor in pathway discrimination.